На книжную полку - Каревина, Е. (Социология: теория, методы, маркетинг, 2000)
Рецензия на книгу: Ukraine: the search for a national identity / Ed. by S.L. Wolchik and V.Zviglyanich. Rowmans & Littlefield Publishers, inc., 2000. 310 p.